Cyclone Freddy and its impact on maternal health service utilisation: Cross-sectional analysis of data from a national maternal surveillance platform in Malawi. - Hussein H Twabi; James Jafali; Leonard Mndala; Jennifer Riches; Edward J M Monk; Deborah Phiri; Regina Makuluni; Luis Gadama; Fannie Kachale; Rosemary Bilesi; Malangizo Mbewe; Andrew Likaka; et al. (PLOS Global Public Health, 2024)
Climate change poses a significant threat to women's health in sub-Saharan Africa, yet the impact of climate change on maternal health is rarely reported in the region. Using an existing Maternal Surveillance Platform (MATSurvey), we estimated the immediate impact of Cyclone Freddy on maternal health care service indicators in Malawi. We analysed facility-level data for pregnant women up to 42 weeks post-partum using the national MATSurvey database. We compared incidences of service utilisation before (1 January to 19 February 2023) and after (20 February to 30 March 2023) the cyclone using a negative binomial regression approach. Between 1 January and 30 March 2023, a total of 37,445 live births, 50,048 antenatal clinic attendances, 23,250 postnatal clinic attendances, 84 maternal deaths, and 1,166 neonatal deaths were recorded by 33 facilities in the MatSurvey database. There was an immediate reduction in service utilisation in the post-cyclone period, including the postnatal attendance per week (pre-cyclone median: 355.0 [IQR 279.0-552.0], post-cyclone median: 261.0 [IQR 154.3-305.5], RR 0.56 [95% CI 0.44-0.71, p <0.001]) and the antenatal attendance per week (pre-cyclone median: 860.0 [IQR 756.5-1060.0], post-cyclone median: 656.5 [IQR 486.5-803.3], RR 0.66 [95% CI 0.55-0.78, p <0.001]). Stratified analyses by geographical zones revealed a stronger reduction in postnatal clinic attendance in the Southwest (RR 0.50 [95% CI 0.29-0.85, p = 0.010]) and the North (RR 0.29 [95% CI 0.15-0.56, p <0.001]). Cyclone Freddy resulted in an immediate decline in utilisation of maternal health services in cyclone-affected regions in Malawi. We observe evidence of catastrophic climate events impacting on the healthcare of women and their babies. Policymakers, researchers, and health systems need to ensure that essential women's health services are maintained during these events and improve measures to support service resilience in the face of climate change.